Domain knowledge and communications: a framework for mobile learning and organisations. (18th October 2007) - Chong, P. Pete; Chen, Jason C.H.
The design of an effective learning/teaching system must take into account both the contents management and the delivery tools; i.e. the knowledge to be learned and the communication methods. This paper discusses a general framework to depict the interaction of the knowledge contents and the components of communication tools that are involved in their delivery.